Assessment of Knowledge, Attitude, and Practice of Recent Diagnostic Aids for Oral Cancer among Dental Students - Manju J; Krithika C; Sharmila. S; Siva Kumar. S; Soniya. H; Sri Hamsika. N (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: The aim of the present study was to assess the knowledge, attitude and practice of recent diagnosticaids for oral cancer among dental students.Materials and Methods: This study was conducted among 100 students using a 15-item self-administeredquestionnaire during COVID-19 pandemic period involving both undergraduates and postgraduate dentalstudents.It was formatted on google forms and shared through social media. The data collected was analysedstatistically.Results: A total of 100 dental studentsparticipated in the survey. The total knowledge, attitude, and practiceabout recent diagnostic aids for oral cancer (based on summing all the positive responses -- for all therelevant questions -- and calculating the percentage) was 90% for post-graduates (highest), 88% for internsgroup, 84% for final years and 80% for third years (least) respectively.The results of this study show thatpostgraduates had good knowledge about recent diagnostic aids for oral cancer when compared to othergroups.Conclusion: These findings concerning dental students suggests that they have sufficient knowledge in therecent diagnostic methods of oral canceras they are the ones who have higher chances of diagnosing oralcancer at earlier stages as they routinely examine oral cavity.